Pengaruh model creative problem solving terhadap motivasi belajar pendidikan Pancasila Siswa Madrasah Aliyah - Widiya Julita; Hambali Hambali; Indra Primahardani (Departemen Pendidikan Kewarganegaraan dan Ilmu Hukum Universitas Negeri Padang, 2026)
The Influence of the Creative Problem Solving Learning Model on the Motivation to Learn Pancasila Education of Class X Students of MAN Insan Cendekia Siak. This study aims to determine the effect of the application of the Creative Problem Solving (CPS) learning model on the learning motivation of Pancasila Education of class X students of MAN Insan Cendekia Siak. The background of this study is that student learning motivation in the Pancasila Education subject tends to be inconsistent due to the dominance of conventional methods centered on the teacher. The study used a quantitative method with a quasi-experimental pretest-posttest control group design. The study population was all class X students (144 students), with a sample of 2 classes (48 students) selected through simple random sampling after a homogeneity test. The experimental class (X-B) used the CPS model, while the control class (X-A) used conventional learning. Data were collected through a learning motivation questionnaire, observation, and documentation, analyzed using normality tests, homogeneity tests, and independent t-tests with SPSS 26 at a significance level of α = 0.05. The results showed that the learning motivation of the experimental class increased significantly from an average pretest of 52.29 to a posttest of 94.58 (very high category), while the control class increased from 47.92 to 60.63 (high category). The t-test resulted in t-count > t-table (p = 0.000 < 0.05), so Ha was accepted and H0 was rejected. Observations of teacher and student activities reached the